2021
DOI: 10.23917/jep.v22i1.11180
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Foreign Direct Investment Inflows in Seven ASEAN Countries During the Period of 2010-2017: Dunning Model Approach

Abstract: Before the monetary crisis in 1998, ASEAN was one of the main objectives of Foreign Direct Investment (FDI) and after the crisis, FDI inflows in ASEAN were still fluctuating, but tended to slowly increase. However, in 2009, there was a drastic decline in the FDI. The study aims to establish the determinants of FDI Inflows in 7 ASEAN countries in the period of 2010-2017. This study employs quantitative analysis through the Dunning Model Approach. As the technique of analysis, the Panel Data Regression analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
1
4
0
1
Order By: Relevance
“…In line with the results obtained in this study that credit and FDI can be used to formulate long-term policies in an effort to overcome unemployment (Setyadharma & Fadhilah, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…In line with the results obtained in this study that credit and FDI can be used to formulate long-term policies in an effort to overcome unemployment (Setyadharma & Fadhilah, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…In the past few decades, the volatility of exchange rates has affected investment decisions and profits in various companies due to the uncertain cost of raw materials if the raw materials are imported from other countries (Latief and Lefen, 2018). When the local currency depreciates, production costs will decrease and foreign investors will wait for the opportunity to put in more funds to increase production at that time (Setyadharma and Fadhilah, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Corruption is an additional expense that must be paid by companies or investors for income tax and other costs (Chamisa, 2020). Previous studies by Nairobi and Afif (2022) and Setyadharma and Fadhilah (2021) found that foreign direct investment is impacted significantly and positive by CPI. However, Chamisa found that not all countries with low CPIs have greater foreign direct investment.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It influences employment scenarios, production, prices, income, imports, exports, the general welfare of recipient countries, and the balance of payments. It is an essential source of economic growth (Cieślik & Ghodsi, 2021;Setyadharma & Fadhilah, 2021).…”
Section: Foreign Direct Investmentmentioning
confidence: 99%